My father's glory La gloire de mon pere - Caubere, Philippe, 1950-; Pagnol, Marcel, 1895-1974.; Pagnol, Marcel, 1895-1974.; Robert, Yves, 1920-2002.; Roussel, Nathalie; Gaumont (Firm); MGM Home Entertainment Inc.; MGM/UA Home Video (Firm) (New York : MGM Home Entertainment, 2002)
Based on the childhood memoirs of Marcel Pagnol, author of Jean de Florette and Manon des Sources, La Gloire de Mon Pre and its companion Le Chateau de Ma Mre are two of the greatest and most successful French films ever made. An adult Marcel fondly recalls one idyllic summer spent with his family in the hills of Provence. A love affair with the country began and during those sundrenched, perfect days he found new respect for his school-teacher father as he adapted to life away from the city. One of cinema's finest celebrations of childhood, My Father's Glory is filled with warmth, humour and nostalgia for the bygone days of a youth spent among the rocky hills of turn-of-the-century Provence.
The enchanting story of Marcel Pagnol's childhood in the south of France, and a very special summer when he was 11 years old. In the countryside of Provence he fell under the spell of the rugged hills, made new friends and strengthened the unique bond with his father.
Based on the work of Marcel Pagnol.
DVD release of the 1991 motion picture.
DVD.
Madman Entertainment: MMA2903.
Produced by Gaumont in collaboration with Gaumont Production, Productions De La Gueville, and TFI Production with the participation of le Centre National de la Cinematographie.
Region4 on Sanity.
Keywords: Pagnol, Marcel, -- 1895-1974 -- Drama; Biographical films; Families in motion pictures; Feature films; Foreign films; Motion pictures, French; Video recordings for hard of hearing people